Development of Resistance in Escherichia coli Against Repeated Water Disinfection - Daer, Sahar; Rehmann, Emily; Rehmann, Jessica; Ikuma, Kaoru (Frontiers in Environmental Science, 2022)
Pathogen resistance against common disinfectants in drinking water treatment could have serious public health implications, particularly in potable water reuse. Frequent disinfection in potable water reuse has a potential to facilitate resistance development. This study investigated resistance development in Escherichia coli against repeated monochloramine and ferrate disinfection. E. coli cultures repeatedly treated with monochloramine developed resistance after 12+ treatment rounds, whereas repeated ferrate disinfection did not lead to resistance development. Monochloramine induced cells into the viable but nonculturable (VBNC) state in initial disinfection rounds; however, repeated monochloramine treatment caused increases in culturability, which corresponded to decreases in the fraction of VBNC cells post-disinfection. The cumulative number of disinfection episodes (~12 times) rather than treatment frequency (e.g., every 48, 96, or 144 h) played a critical role in resistance development against monochloramine. In addition to preventing resistance, ferrate effectively inactivated (>3-log10) the evolved monochloramine-stressed cultures, suggesting that the evolutionary adaptations against monochloramine were ineffective against ferrate. The lack of resistance against ferrate renders it a promising disinfection agent that deserves further assessment. This work's findings demonstrate that repeated disinfection coupled with the type of applied disinfectant can influence bacterial resistance development. Therefore, current and future water disinfection schemes, especially within potable water reuse, need regular monitoring to evaluate the resistance profile of pathogenic bacteria.